Reversal of pancreatic desmoplasia by re-educating stellate cells with a tumour microenvironment-activated nanosystem - Xuexiang Han (Nature Portfolio, 2018)
Stromal-tumour interactions play an important role in pancreatic cancer progression. Here, they describe the development of a tumour microenvironment-responsive gold nanoparticle system incorporating all-trans retinoic acid (ATRA) and siRNA against heat shock protein 47 (HSP47), for use in pancreatic cancer treatment.